Radial Distribution Pattern of Pectin Methylesterases across the Cambial Region of Hybrid Aspen at Activity and Dormancy - Micheli, Fabienne (American Society of Plant Physiologists, 2000)
Biochemical microanalysis combined with tangential cryosectioning was used to visualize the distribution of pectin methylesterases (PMEs) across the cambial region in active and dormant hybrid aspen (Populus tremula L. × Populus tremuloides Michx). These novel techniques allowed us to relate activity and isoforms of PMEs to specific tissues and developmental stages of the stem to get more information on the physiological function of PMEs in cambial growth. Isoelectrofocusing analysis revealed numerous isoforms that were differentially distributed according to the tissue-type and to the cambial stage. A neutral isoform was found to be distributed ubiquitously across the stem of both active and dormant trees, which suggests that it is a housekeeping isoform involved in the maintenance of the cell wall integrity throughout the stem. In addition, two distinct isoforms having different isoelectric points were found to be related to the differentiation of cambial derivatives. A basic isoform appears to be a physiological marker of the dormant stage involved in the cessation of meristematic radial growth, whereas an acidic isoform is functionally related to the immediate expansion of the cambial daughter cells that occurs bilaterally on each side of the cambium at the active stage.